Постановка задачи вычислительного алгоритма по многолучевой раз - Кравец, Н. В. (ХНУРЕ, 2020)
The advantages of the method of radio-acoustic sounding (RASS) are that atmospheric air acts on the acoustic package, which is highly sensitive. The electromagnetic wave transmits information about the state of the package, which is significantly less sensitive than the acoustic wave. This allows you to save and further obtain a significant amount of information using such a sensing system. The procedure for extracting the final information is tightly connected with the parameters of the hardware complex. Therefore, to extract it, you can use microcontroller technology. The algorithm should include complex parameters and signal processing techniques.
Keywords: радиоакустическое зондирование; электромагнитная волна; корреляционные функции поля антенны